The Digital Circular Economy: Technological Innovation Strategies for Production and Concumption Efficiency - Gusti Lanang Putu Tantra; Ngurah Wisnu Murthi (PT. Anagata Sembagi Education, 2026)
The increasing environmental and resource pressures associated with linear economic models have intensified interest in the circular economy as a pathway toward sustainable production and consumption. At the same time, rapid advances in digital technologies have transformed how economic systems operate, creating new opportunities to enhance efficiency through data-driven coordination and optimization. This study examines the digital circular economy as an integrated framework in which technological innovation strategies support both production and consumption efficiency. Using a qualitative descriptive–analytical approach with a conceptual–strategic perspective, the study analyzes academic literature, policy documents, and strategic reports on circular economy and digital innovation. The findings indicate that digital technologies play a critical role in enabling system-level efficiency by improving process optimization, reducing waste, enhancing transparency, and reshaping consumption behavior through digital platforms and feedback mechanisms. However, the study also finds that the transformative potential of the digital circular economy depends on the strategic integration of technology with circular principles, organizational practices, and governance frameworks. The research concludes that the digital circular economy offers a viable pathway toward sustainable efficiency only when digital innovation is aligned with systemic circular objectives rather than applied as isolated technological solutions